Enhancement of near-infrared emission of neodymium-doped monoclinic gadolinium phosphate nanophosphors by surface coating with calcium phosphate. Issue 4 (2nd October 2019) - Watanabe, Mizuki; Yamamoto, Norifumi; Matsuo, Tomoaki; Oka, Ryohei; Ida, Shintaro; Masui, Toshiyuki
ABSTRACT: Core/shell-type nanoparticles composed of GdPO4 : x mol% Nd 3+ /calcium phosphate (CaPO) (0 ≤ x ≤ 5) were synthesized by a precipitation method, as nontoxic bio imaging phosphors that can emit near-infrared (NIR) light under NIR excitation. The GdPO4 : x mol% Nd 3+ core, obtained in a single-phase form of the monoclinic rare-earth orthophosphate structure, exhibited characteristic emissions attributed to the f–f transitions of Nd 3+ . The strongest emission peak was observed at 1061 nm under excitation at 800 nm in a sample containing 3 mol% of Nd 3+ . The average particle size of GdPO4 : 3 mol% Nd 3+ was 42 nm, indicating that nano-sized particles were successfully obtained. Although the average particle size of the core/shell-type GdPO4 : 3 mol% Nd 3+ /CaPO nanophosphor was slightly increased to 54 nm by a second calcination in the surface coating process, the CaPO shell was well formed with a thickness of 3 nm around the GdPO4 : 3 mol% Nd 3+ core. With surface coating with the CaPO4 shell, the NIR emission intensity increased to 4.2 times higher than that of GdPO4 : 3 mol% Nd 3+ . This emission intensity was significantly higher than that of indocyanine green, moreover, which is used in practice as an organic bioimaging reagent.